2006
DOI: 10.1096/fj.05-4780fje
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental type 1 diabetes and exercise training on angiogenic gene expression and capillarization in skeletal muscle

Abstract: Diabetes alters microvascular structure and function and is a major risk factor for cardiovascular diseases. In diabetic skeletal muscle, impaired angiogenesis and reduced VEGF-A expression have been observed, whereas in healthy muscle exercise is known to have opposite effects. We studied the effects of type 1 diabetes and combined exercise training on angiogenic mRNA expression and capillarization in mouse skeletal muscle. Microarray and real-time PCR analyses showed that diabetes altered the expression of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
120
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 54 publications
7
120
2
1
Order By: Relevance
“…Many beneficial effects of exercise such as increasing insulin sensitivity, improved glucose uptake and alleviating diabet complications in diabetic animals and patients are reported. [4][5][6][7][8] Exercise is a modifiable behavioral factor which can produce several beneficial effects, including improved cardiac functions and diabetes complications. 9 Exercise training has been reported to increase SOD 10,11 and also partially reverses oxidative stress in the brains of ethanol-exposed rats.…”
Section: Introductionmentioning
confidence: 99%
“…Many beneficial effects of exercise such as increasing insulin sensitivity, improved glucose uptake and alleviating diabet complications in diabetic animals and patients are reported. [4][5][6][7][8] Exercise is a modifiable behavioral factor which can produce several beneficial effects, including improved cardiac functions and diabetes complications. 9 Exercise training has been reported to increase SOD 10,11 and also partially reverses oxidative stress in the brains of ethanol-exposed rats.…”
Section: Introductionmentioning
confidence: 99%
“…Other human studies of cardiac adjustments to exercise training in type 1 diabetes are sparse. Vascular dysfunction is also evident in type 1 diabetes (Kindig et al 1998, Järvisalo et al 2004, Kivelä et al 2006, Mason et al 2006, probably having an independent limiting influence on muscle blood flow and therewith O 2 delivery also during exercise (Rissanen et al 2015). Aerobic training enhances endothelial function (Fuchsjäger-Mayrl et al 2002) and leads to muscle capillary neoformation (Wallberg-Henriksson et al 1982) in type 1 diabetes patients, and has also been shown to increase the expression of pro-angiogenic genes in type 1 diabetes mice (Kivelä et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Vascular dysfunction is also evident in type 1 diabetes (Kindig et al 1998, Järvisalo et al 2004, Kivelä et al 2006, Mason et al 2006, probably having an independent limiting influence on muscle blood flow and therewith O 2 delivery also during exercise (Rissanen et al 2015). Aerobic training enhances endothelial function (Fuchsjäger-Mayrl et al 2002) and leads to muscle capillary neoformation (Wallberg-Henriksson et al 1982) in type 1 diabetes patients, and has also been shown to increase the expression of pro-angiogenic genes in type 1 diabetes mice (Kivelä et al 2006). However, animal (Kivelä et al 2006), cross-sectional (Mason et al 2006), and short-term training intervention (Wallberg-Henriksson et al 1984) studies have suggested that these vascular effects would be deficient relative to individuals without diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations